An Investigation into the Strategies Used by the English-Majored Students at Tay Do University in Translating Vietnamese-English Cultural Expressions (British Journal of Multidisciplinary and Advanced Studies, 2025)
Translation is a useful skill in linguistic learning. However, it is not easy for students to master this skill due to the cultural differences. Therefore, the purpose of this research is to focus on some difficulties of English majored students in Vietnamese - English cultural translation. Specifically, this study is to figure whether English majored students at Tay Do University encounter difficulties in translating cultural expressions from Vietnamese into English. In the study process, the translation test and interview were used as the instruments to collect the data. The participants were 60 English majored freshmen and seniors at Tay Do University. The results of the study pointed out that the English-majored students had difficulties in Vietnamese-English translation. It is hoped that this research can be helpful for not only students but also teachers in the process of learning and teaching translation.